Defending Irreversibility and Brain Death in the Ethics of Heart Donation After Circulatory Death - Machado, Calixto (Bioethics, 2026)
Heart donation after circulatory determination of death (DCDD) expands the donor pool but requires careful ethical grounding, particularly regarding the determination of death. This article affirms the legitimacy of brain death as a medically and ethically valid form of death, emphasizing that the irreversible cessation of brain function remains the foundational criterion. Building upon the framework proposed by Bernat and Dalle Ave, the essay promotes the concept of Donation after Brain Circulation Determination of Death (DBCDD), which ensures death is defined by the permanent cessation of brain circulation, leading inevitably to the loss of all brain function. It argues for the necessity of safeguards in DCDD protocols, including strict verification of systemic circulatory arrest and clear exclusion of cerebral reperfusion. Rather than undermining the legitimacy of DCDD, these standards uphold the integrity of brain-based death determination, reinforce the dead donor rule, and safeguard public trust. This approach unifies death determination under the brain criterion across all clinical pathways.